VARIABILITY IN PHYSICAL, CHEMICAL AND HYDRAULIC PROPERTIES OF AGRICULTURAL SOIL IN SOUTHWEST NIGERIA - ADEBOYE , O. B.; OLAPADE , M. O.; ADEBOYE , A. P.; TIJANI, F. O.; SHITTU , K. A.; ADEKALU , K. O.; OSUNBITAN , J. A. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The properties of soil play significant roles in soil productivity. The study aimed at determining the variability in physical, chemical and hydraulic properties of agricultural soils and their implications for crop production in seven farmlands in the Southwest Nigeria. Textural class, bulk density at 0-30 and 30-60 cm, hydraulic conductivity, water repellency and contact angle were determined using standard techniques. The farmlands were predominantly sandy loam soil. Bulk density ranged from 1.14 g cm-3 in the upper 30 cm at Oyo to 1.53 g cm-3 in the lower 30-60 cm at Mokore. Organic matter ranged from 0.74 % in 30-60 cm at Mokore to 3.62 % in 0-30 cm at Oyo. Hydraulic conductivity was higher in the upper 30 cm of the soil than the lower layer. This implies that the soil in the area is well drained and water logging during rainy season will be minimal. Contact angles for sandy loam soil ranged from 20.8 to 72.2o. Repellency index ranged from 1.07 for NIHORT to 3.27 for Ijebu-Igbo. Most of the soils in the area were hydrophobic and had high sub-critical repellency for water. There was strong correlation between contact angle and repellency index (r2 = 0.98, p < 0.0001), weak correlation between contact angle and organic matter (r2 = 0.14, p = 0.18). Sustainable engineering measures and agronomic practices will be required to ensure optimum use of land resources in the areas.